CODE-SWITCHING IN ZHAFIRA AQYLA YOUTUBE VIDEO: A SOCIOLINGUISTIC STUDY - Parinduri, Afrahul Fadhillah; Chaterina Manalu, Lidya Arella; Lekson, Mutiara Alda; Alfia, Fila; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Lampung, 2024)
This study investigates the phenomenon of code-switching in the YouTube video titled